Concentrations of cadmium and selected essential elements in malignant large intestine tissue - Klimczak, Michał; Dziki, Adam; Kilanowicz, Anna; Sapota, Andrzej; Duda-Szymańska, Joanna; Daragó, Adam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Colorectal cancer is one of the most common cancers worldwide. Incidence rates of large intestine cancer indicate a role of environmental and occupational factors. The role of essential elements and their interaction with toxic metals can contribute to the explanation of a complex mechanism by which large intestine cancer develops. Bearing this in mind, determining the levels of essential and toxic elements in tissues (organs), as well as in body fluids, seems to shed light on their role in the mode of action in malignant disease. Aim : Determination of the levels of cadmium, zinc, copper, selenium, calcium, magnesium, and iron in large intestine malignant tissue. Material and methods : Two intraoperative intestine sections were investigated: one from the malignant tissue and the other one from the normal tissue, collected from each person with diagnosed large intestine cancer. Cadmium, zinc, copper, calcium, magnesium, and iron levels were determined with atomic absorption spectrometry, and selenium levels by spectrofluorimetric method. Results : The levels of copper, selenium, and magnesium were higher in the malignant than in normal tissues. In addition, the zinc/copper and calcium/magnesium relationship was altered in malignant tissue, where correlations were lower compared to non-malignant tissue. Conclusions : The results seems to demonstrate disturbed homeostasis of some essential elements. However, it is hard to confirm their involvement in the aetiology of colorectal cancer.